Beyond the red notebook : essays on Paul Auster - Barone, Dennis (Penn studies in contemporary American fiction., 1995)
The novels of Paul Auster--finely wrought, self-reflexive, filled with doublings, coincidences, and mysteries--have captured the imagination of readers and the admiration of many critics of contemporary literature. In Beyond the Red Notebook, the first book devoted to the works of Auster, Dennis Barone has assembled an international group of scholars who present twelve essays that provide a rich and insightful examination of Auster's writings. The authors explore connections between Auster's poetry and fiction, the philosophical underpinnings of his writing, its relation to detective fiction, and its unique embodiment of the postmodern sublime. Their essays provide the fullest analysis available of Auster's themes of solitude, chance, and paternity found in works such as The Invention of Solitude, City of Glass, Ghosts, The Locked Room, In the Country of Last Things, Moon Palace, The Music of Chance, and Leviathan.This volume includes contributions from Pascal Bruckner, Marc Chenetier, Norman Finkelstein, Derek Rubin, Madeleine Sorapure, Stephen Bernstein, Tim Woods, Steven Weisenburger, Arthur Saltzman, Eric Wirth, and Motoyuki Shibata. The extensive bibliography, prepared by William Drenttel, will greatly benefit both scholars and general readers.